Different Occlusal Schemes in a Persistent Protruding Complete Denture Wearer - Carolina Mayumi Iegami; Danilo de Melo Lopes; Atlas Edson Moleros Nakamae; Priscila Nakasone Uehara; Regina Tamaki (Case Reports in Dentistry)
Different types of artificial teeth and occlusal designs can be used in complete dentures. Bilateral balanced occlusion, lingualized occlusion, canine guidance, and monoplane are the main occlusal designs; however there is no agreement on which tooth arrangement is ideal for achieving success in complete dentures. This report presents an alternative for persistent involuntary protruding complete denture wearers through the use of artificial teeth with higher cusps. Due to an old and worn pair of complete dentures, the patient had the habit of protruding. New dentures were made with Biotone artificial teeth and in the trial session, the patient would still protrude. A new set was made with Premium artificial teeth, which present higher cusps. With these dentures, the involuntary protrusion did not occur. From the delivery to the follow-up sessions, the patient stopped protruding.